Development of nuclear and chloroplast microsatellite markers for the endangered conifer Callitris sulcata (Cupressaceae)1. (10th August 2015) - Sakaguchi, Shota; Lannuzel, Guillaume; Fogliani, Bruno; Wulff, Adrien S.; L'Huillier, Laurent; Kurata, Seikan; Ueno, Saneyoshi; Isagi, Yuji; Tsumura, Yoshihiko; Ito, Motomi
Abstract : Premise of the study: Microsatellite markers were developed for Callitris sulcata (Cupressaceae), an endangered conifer species in New Caledonia. Methods and Results: Using sequencing by synthesis (SBS) of an RNA‐Seq library, 15 polymorphic nuclear and chloroplast microsatellite markers were developed. When evaluated with 48 individuals, these markers showed genetic variations ranging from two to 15 alleles and expected heterozygosity ranging from 0 to 0.881. Conclusions: These markers will be useful for examining the genetic diversity and structure of remaining wild populations and improving the genetic status of ex situ populations.